Clays and Clay Minerals, Vol. 56, No. 5, 487–493, 2008. - Suzuki, Yasutaka; Hirakawa, Shoichiro; Sakamoto, Yusuke; Kawamata, Jun; Kamada, Kenji; Ohta, Koji (The Clay Minerals Society, 2008)
Hybrid films consisting of Sumecton SA smectite (SSA) and a diacetylenic two-photon absorptive dye; 1,4-bis(2,5-dimethoxy-4-{2-[4-(N-methyl)pyridinium]ethenyl}phenyl) butadiyne triflate (MPPBT) were fabricated. TheMPPBT-clay composites were prepared by the cation exchange method in a dimethylsulfoxide (DMSO)-water mixed solvent. A low-light-scattering film, suitable for use in optical devices, was obtained by filtration of the dispersion of the MPPBT-clay composites. Estimation of the twophoton absorption cross-section (s(2)) by means of the open-aperture Z-scan technique was performed using the present film. The s(2) value of MPPBT in the film fabricated at the MPPBT loading levels vs. 20% cation exchange capacity was 1030 GM (1 GM = 161050 cm4 s photon-1 molecule-1) at an excitation wavelength of 800 nm. The value was 1.3 times greater than the maximum value of the s(2) of MPPBT dissolved in DMSO without clay.
Hybrid Films Consisting Of A Clay And A Diacetylenic, Two-photon Absorptive Dye
gsccm56501-suz.pdf - 220KB
Keywords: Periodicals; Geology; Diacetylenic Dye; Film; Synthetic Saponite; Two-photon Absorption